Cryopreservation of Bone Marrow Mononuclear Cells Alters Their Viability and Subpopulation Composition but Not Their Treatment Effects in a Rodent Stroke Model - Bing Yang; Kaushik Parsha; Krystal Schaar; Nikunj Satani; Xiaopei Xi; Jaroslaw Aronowski; Sean I. Savitz (Stem Cells International)
The systemic administration of autologous bone marrow (BM) derived mononuclear cells (MNCs) is under investigation as a novel therapeutic modality for the treatment of ischemic stroke. Autologous applications raise the possibility that MNCs could potentially be stored as a banked source. There have been no studies that investigate the effects of cryopreservation of BM-MNCs on their functional abilities in stroke models. In the present study, C57BL/6 mice were subjected to middle cerebral artery occlusion (MCAo) for 60 minutes and then divided into two treatment groups: fresh MNCs versus cryopreserved MNCs. BM-MNCs were collected at 22 hours after MCAo and were stored in liquid nitrogen for 12 months in cryopreserved MNCs group. BM-MNCs cellular viability, composition, and phenotype of the various subpopulations of mice BM-MNCs were evaluated by flow cytometry, and the behavioral recovery of stroke animals was tested with freshly harvested MNCs versus cryopreserved MNCs by corner test and ladder rung test. We found that long-term cryopreservation negatively impacts the cellular viability of bone marrow MNCs. Cryopreservation also alters the cellular composition of various subpopulations within the MNCs. However, despite the changes observed in cryopreserved cells, both fresh and frozen MNCs have similar beneficial effect on behavioral and histological outcomes.